Climate change impact on crop and irrigation water requirements for rice and wheat cultivation in the Tamor River Basin of Nepal - Acharya, Ajay; Shrestha, Sangam; Pandey, Vishnu Prasad (Pathum Thani : Asian Institute of Technology, 2017)
Climate change has its impact on almost every sectors and water sector is one of them. It is a global phenomenon that is hugely responsible for food production because the overall economy of a country is dependent on the scale of productivity. Rice and wheat production has been the major crop in South-East Asia. The natural demand for crop water is not full filled by precipitation water because rainfall is converted to runoff, infiltration etc. and hence effective rainfall is less. The insufficient demand of water for crop growth needs to be full filled and we supply irrigation water. Future climate can play a serious role as irrigation water that is supplied to the field will depend on climatic parameters which implies that researchers or water managers must conduct studies to predict the future irrigation water depending on the current parameters. This study focuses on the impacts that climate change will bring to the irrigation water requirement for rice and wheat cultivation in the Tamor River Basin of Nepal. We use linear bias correction of RCM outputs of the study area to forecast future climate. The estimations of crop and irrigation water requirement for different time windows under climate change scenarios can be conducted using Cropwat Model. The analysis is done in Taplejung district that lies in High Hills region.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Civil and Infrastructure Engineering, School of Engineering and Technology
Capstone Project (B.Sc.)-Asian Institute of Technology, 2017
Keywords: Rice -- Water requirements; Climatic changes -- Nepal; Crops and climate -- Nepal